Management of Corn Flour (Zea Mays Var. Amylacea) as a Staple Food for the Community of South Romleher Hamlet, Wonreli Village, South-West Islands District - Pelmelay, Dorce Lerin; Lasaiba, Mohammad Amin; Latumahina, Fransina (Universitas Pattimura, 2022)
Corn is a vital food commodity that plays a significant role in the Indonesian economy and is a staple food in several regions. This research is of a Qualitative Descriptive nature. The location of this study is Dusun Romleher Selatan, Desa Wonreli, Kecamatan Pulau – Pulau Terselatan. The population in this study consists of 20 individuals, while the sample selected randomly includes 10 individuals. Data collection techniques employed are observation, interviews, and documentary studies. Once the research data is gathered, it will be analyzed using the data analysis techniques chosen by the researcher. The research results indicate that wet milling (soaking) yields more flour than dry milling (without soaking). However, the nutritional content of dry-milled flour is higher. Mechanically processing corn into flour using a degerminator and a flour mill produces a wonderful flour texture.